Socialization and Psychological Determinants of Financial Confidence among Jakarta Stock Investors - Aditya Tri Nugroho; Nuri Wulandari; Mahelan Prabantarikso; Enny Haryanti (UTSAHA: Journal of Entrepreneurship, 2026)
Financial confidence represents a critical determinant in investment decision-making among stock market participants. This study examines the influence of financial socialization and psychological characteristics on financial confidence among stock investors in Jakarta, mediated by digital financial literacy and financial behavior. A quantitative research approach was employed, utilizing SmartPLS 3 software for data analysis through Partial Least Squares Structural Equation Modeling. The sample comprised 50 active stock investors residing in Jakarta, with data collected through structured questionnaires using five-point Likert scales. The analysis revealed four principal findings. First, financial socialization does not significantly influence digital financial literacy (p = 0.200), contradicting conventional socialization theory expectations. Second, psychological characteristics exert a strong positive influence on digital financial literacy (β = 0.902, p < 0.001). Third, digital financial literacy significantly affects financial behavior (β = 0.732, p < 0.001). Fourth, financial behavior strongly influences financial confidence (β = 0.799, p < 0.001). These findings suggest that intrinsic psychological factors serve as more powerful drivers of financial confidence development than external social learning processes among equity investors. The research contributes theoretical insights regarding financial confidence formation in emerging markets and provides practical implications for financial institutions, regulators, and investors. The study recommends that investor education programs prioritize psychological skill development and experiential learning rather than conventional information dissemination approaches.